(untitled) (Advancements in Homeopathic Research, 2022)
The use of allopathic medicines simultaneously with homoeopathic treatment had been condemned by Homoeopathic physicians since the inception of Homoeopathy on the basis of their prejudice that homoeopathic medicines would be neutralized/ antidoted by allopathic medicines.